A vertical water exchange of the groundwater in the central part of Moscow artesian basin - N. V. Fisun (Известия высших учебных заведений: Геология и разведка, 2017)
The hydrogeological features of the central part of the Moscow artesian basin (MAB) under the natural conditions provided the existence of the downward vertical flows of the groundwater, the formation of the fresh underground waters of the Carboniferous complex, desalination of the Upper Devonian subterranean waters. The long exploitation of the Aleksin-Protvino horizon in the central part of the MAB led to the formation of a depression of the piezometric level with a depth of 80 m, as well as a change in the ratio of the absolute marks of the piezometric surfaces of the groundwater of the Lower Carboniferous and the Upper Devonian, and the creation of prerequisites for the changing of the orienfafion of the vertical wafer exchange between them. A map of the difference in pressures between the Aleksin-Protvino and the Upper Devonian horizons, compiled by the author, shows this situation. In a vast zone of the central part of the MAB, the pressure surface of the Alexin-Protvino horizon is 30-50 m below the upper Devonian horizon. Under these conditions, it seems important to study the Upper Devonian aquiferous complex as a possible source of the «contamination» of the groundwater of the Lower Carboniferous, especially in the zones of active lineaments of the Moscow syneclise.